Nutriproteomics survey of sweet chestnut (Castanea sativa Miller) genetic resources in Portugal. (August 2020) - Ribeiro, Miguel; Freitas, Michael; Domínguez-Perles, Raúl; Barros, Ana I.R.N.A.; Ferreira-Cardoso, Jorge; Igrejas, Gilberto
Abstract: Sweet chestnut ( Castanea sativa Miller) is a tree species whose edible fruit was a staple food for many centuries until the emergence of potato and cereal crops. Once of great importance for the survival of rural populations, at present there is a renewed interest in this fruit as a nutritious food, partly due being gluten-free. Portugal is one of the major sweet chestnut producing countries and is an important natural habitat for native European chestnut species. In a nutriproteomics approach, the main objective was to describe and evaluate the sweet chestnut germplasm present in Portugal. Globulins of 22 Portuguese sweet chestnut varieties were used as markers of genetic diversity. This characterization showed significant diversity ( h = 0.334) among the varieties tested, but also a homonymy problem in varietal identification. Two-dimensional electrophoresis and mass spectrometry were then used to further investigate the chestnut proteome. Most of the proteins were assigned as having functions in nutritional storage activity. The photorespiration protein Rubisco, normally present in photosynthesizing plant parts was also present in the fruit which suggests that the catabolism of this protein is unusual in C. sativa species. Furthermore, the Portuguese varieties have been shown to be good sources of essential amino acids, and particularly the 'Bária' variety showed a balanced profile that meets the recommended dietary requirements of older children, adolescents, and adults.